GM‐CSF enhances tumor invasion by elevated MMP‐2, ‐9, and ‐26 expression. (26th November 2012) - Gutschalk, Claudia M.; Yanamandra, Archana K.; Linde, Nina; Meides, Alice; Depner, Sofia; Mueller, Margareta M.
Abstract Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) promotes tumor progression in different tumor models in an autocrine and paracrine manner. However, at the same time GM‐CSF is used in cancer therapies to ameliorate neutropenia. We have previously shown in GM‐CSF and G‐CSF expressing or negative skin or head and neck squamous cell carcinoma that GM‐CSF expression is associated with a highly angiogenic and invasive tumor phenotype. To determine the functional contribution of GM‐CSF to tumor invasion, we stably transfected a GM‐CSF negative colon adenocarcinoma cell line HT‐29 with GM‐CSF or treated the same cell line with exogenous GM‐CSF. While GM‐CSF overexpression and treatment reduced tumor cell proliferation and tumor growth in vitro and in vivo, respectively, it contributed to tumor progression. Together with an enhanced migratory capacity in vitro, we observed a striking increase in tumor cell invasion into the surrounding tissue concomitant with the induction of an activated tumor stroma in GM‐CSF overexpressing or GM‐CSF treated tumors. In a complex 3D in vitro model, enhanced GM‐CSF expression was associated with a discontinued basement membrane deposition that might be mediated by the increased expression and activation of MMP‐2, ‐9, and ‐26. Treatment with GM‐CSF blocking antibodies reversed this effect. The increased presence and activity of these tumor cell derived proteases was confirmed in vivo. Here, expression of MMP‐26 protein was predominantly located in pre‐ and early‐invasive areas suggesting MMP‐26 expression as an early event in promoting GM‐CSF dependent tumor invasion.